Preparation method of temperature-sensitive poly (N-vinylcaprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity
By grafting polyN-vinyl caprolactam on the inner wall of the titanium dioxide hollow ball, a temperature-sensitive polyN-vinyl caprolactam grafted titanium dioxide hollow ball catalyst with high catalytic activity was prepared, which solved the problem of low natural light utilization rate and insufficient catalytic activity of the photocatalyst, and achieved a more efficient photocatalytic degradation effect.
Patent Information
- Application Number
- CN202510028421.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The band gap of existing photocatalysts such as pure titanium dioxide is wide, resulting in a low utilization rate of natural light. One-dimensional and two-dimensional titanium dioxide photocatalysts are prone to agglomeration and small specific surface area during preparation and application, which limits the improvement of their catalytic activity.
The preparation method of a temperature-sensitive polyN-vinyl caprolactam grafted titanium dioxide hollow sphere catalyst is adopted. By grafting polyN-vinyl caprolactam on the inner wall of the titanium dioxide hollow sphere, the photoresponse range of the photocatalyst is broadened and its catalytic activity is improved.
The photocatalyst has achieved higher utilization rate and specific surface area of natural light, significantly improved catalytic activity and recycling, and can more effectively degrade pollutants in wastewater.
Smart Images

Figure CN119823404A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, in particular to a method for preparing a temperature-sensitive poly-N-vinyl caprolactam grafted titanium dioxide hollow sphere catalyst with high catalytic activity. Background Art
[0002] In recent years, photocatalytic oxidation technology has been widely used in the field of wastewater treatment due to its low raw material preparation cost and high catalytic activity. The core lies in the fact that photocatalysts can absorb natural light of a specific wavelength and then produce active free radicals, which can degrade pollutants in wastewater. Among many photocatalysts, titanium dioxide is recognized as the best photocatalyst due to its strong oxidizing property, good stability and corrosion resistance. However, the band gap of pure titanium dioxide is relatively wide, which means that it can only effectively absorb ultraviolet light and its utilization rate of sunlight is relatively low. In addition, one-dimensional and two-dimensional titanium dioxide photocatalysts are prone to agglomeration during preparation and application, and have a small specific surface area, which further limits the improvement of their catalytic activity. Therefore, improving the utilization rate of natural light by photocatalysts and increasing their specific surface area have become the key to improving catalytic activity.
[0003] In order to overcome these limitations, researchers have begun to focus on mesoporous hollow sphere materials. This material has unique optical and photoelectrochemical properties, such as strong light capture ability, large specific surface area and stable three-dimensional spherical structure. Moreover, by combining surface modification methods, the light absorption range of photocatalysts can be further expanded, which is of great significance to the application of titanium dioxide photocatalysts. However, surface modification methods are usually limited to modifying the outer wall of titanium dioxide hollow spheres. When responsive materials are grafted onto the outer wall of these titanium dioxide hollow spheres, the resulting composite materials are often easily disturbed by the external environment (such as temperature, humidity and other factors), which in turn causes a decrease in catalytic activity. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a thermosensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity, which can expand the response range to light and improve the catalytic activity.
[0005] The technical solution of the present invention is: A method for preparing a thermosensitive poly-N-vinyl caprolactam grafted titanium dioxide hollow sphere catalyst with high catalytic activity, the specific steps of which are as follows: (1) Preparation of titanium dioxide-encapsulated silica nanoparticles or carbon spheres Ultrasonic dispersion of silica nanoparticles or carbon spheres in anhydrous ethanol, addition of hexadecylamine and ammonia, and dropwise addition of tetrabutyl titanate, wherein the mass volume ratio of the silica nanoparticles to the tetrabutyl titanate is 4:11 g / mL, to prepare anatase titanium dioxide-encapsulated silica nanoparticles or carbon spheres; (2) Preparation of titanium dioxide hollow spheres The anatase titanium dioxide-coated silicon dioxide nanoparticles are ultrasonically dispersed in a sodium hydroxide solution and reacted at 60° C. for 3 hours to obtain a crude product; the product is centrifuged, washed, and dried; or the anatase titanium dioxide-coated carbon spheres are calcined at 550° C. to obtain titanium dioxide hollow spheres; (3) Synthesis of ammonia functionalized titanium dioxide hollow spheres (TiO 2 -HSs-NH 2 ) Titanium dioxide hollow spheres (TiO 2 -HSs) and 3-aminopropyltriethoxysilane (APTES) were ultrasonically dispersed in toluene, the mass volume ratio of the titanium dioxide hollow sphere to 3-aminopropyltriethoxysilane was 0.1:3 g / mL, and the reaction was refluxed at 70°C for 12 h to obtain a crude product, which was centrifuged, washed, and vacuum dried to obtain an amine-functionalized titanium dioxide hollow sphere (TiO 2 -HSs-NH 2 ); (4) Synthesis of aldehyde-functionalized titanium dioxide hollow spheres (TiO 2 -HSs-CHO) The ammonia-functionalized titanium dioxide hollow spheres were ultrasonically dispersed in a glutaraldehyde aqueous solution, wherein the mass volume ratio of the ammonia-functionalized titanium dioxide hollow spheres to the glutaraldehyde aqueous solution was 0.1:6 g / mL, and the mixture was stirred and reacted at 25° C. for 4 h to obtain a crude product, which was centrifuged, washed, and vacuum dried to obtain aldehyde-functionalized titanium dioxide hollow spheres (TiO 2 -HSs-CHO); (5) Synthesis of poly (N-vinyl caprolactam@titanium dioxide hollow sphere catalyst (PNVCL@TiO 2 -HSs) Hydrogen chloride gas was introduced into 1,4-dioxane until the pH value was 5, N-vinyl caprolactam, azobisisobutyronitrile and mercaptoethylamine were added and ultrasonically dispersed uniformly, and then aldehyde-functionalized titanium dioxide hollow spheres (TiO 2-HSs-CHO), continue ultrasonic dispersion, the mass ratio of N-vinyl caprolactam, azobisisobutyronitrile, mercaptoethylamine and synthetic aldehyde functionalized titanium dioxide hollow sphere is 1.5:0.03:0.02:0.3, stir for 12 hours at 25°C in a nitrogen environment, heat to 68°C, reflux and stir for 24 hours, centrifuge and wash to obtain a crude product; the crude product is ultrasonically dispersed in an ammonia solution with a pH value of 7-8, stirred at 25°C for 6 hours, recovered by centrifugation, washed, and vacuum dried to obtain a poly N-vinyl caprolactam@titanium dioxide hollow sphere catalyst (PNVCL@TiO 2 -HSs).
[0006] Furthermore, the aldehyde-functionalized titanium dioxide hollow sphere (TiO 2 The mass volume ratio of -HSs-CHO) to 1,4-dioxane is 3:500 g / mL.
[0007] Furthermore, the silicon dioxide nanoparticles are prepared by using the classical Prepared by the method.
[0008] Further preferably, the preparation process of silica nanoparticles is as follows: deionized water is added to anhydrous ethanol, and after stirring evenly, ammonia water is poured into a beaker, and the volume ratio of anhydrous ethanol to ammonia water is 18.72:1. After stirring evenly, tetraethyl silicate is added dropwise, and the volume ratio of tetraethyl silicate to ammonia water is 5.6:3.125. The reaction is stirred at 25°C for 1h to obtain a crude product, which is centrifuged, washed, and dried in a drying oven at 60°C to obtain silica nanoparticles.
[0009] Further preferably, the volume ratio of the deionized water to anhydrous ethanol is 10:58.5.
[0010] Furthermore, the concentration of the sodium hydroxide solution in step (2) is 1 mol / L.
[0011] Further preferably, the amount of sodium hydroxide solution added is 60.0 mL of sodium hydroxide solution per gram of anatase titanium dioxide-encapsulated silicon dioxide nanoparticles.
[0012] Furthermore, the volume ratio of glutaraldehyde to deionized water in the glutaraldehyde aqueous solution is 1:2.
[0013] Under stirring conditions, the monomer N-vinyl caprolactam, the initiator azobisisobutyronitrile and the chain transfer agent mercaptoethylamine are introduced into the cavity through the mesopores on the aldehyde-functionalized titanium dioxide wall; at a certain temperature, the monomer N-vinyl caprolactam in the hollow sphere is polymerized; the amino-terminated poly N-vinyl caprolactam reacts with the aldehyde-functionalized titanium dioxide hollow sphere through Schiff base reaction to obtain the photocatalytic composite material poly N-vinyl caprolactam@titanium dioxide hollow sphere. Its beneficial effects are: (1) Compared with traditional preparation methods, the required chemical reagents are common and easily available, the equipment is easy to operate, and the prepared photocatalyst has high catalytic activity and recyclability.
[0014] (2) By polymerizing N-vinyl caprolactam in the inner cavity and reacting it with aldehyde-functionalized titanium dioxide hollow spheres, a poly-N-vinyl caprolactam@titanium dioxide hollow sphere composite material is formed. This modification effectively broadens the light response range of the photocatalytic composite material, enabling it to receive and utilize more photons, thereby improving the photocatalytic activity.
[0015] (3) The introduction of poly (N-vinyl caprolactam) not only enhances the stability of the composite material, but also promotes the generation of more active free radicals, which can more effectively degrade pollutants in wastewater and significantly improve the catalytic activity of the composite material.
[0016] (4) Compared with grafting thermosensitive polymers on the outer wall of titanium dioxide hollow spheres, the poly (N-vinyl caprolactam)@titanium dioxide hollow spheres prepared in the present invention exhibit good dispersibility in the dye solution, which helps to fully contact the photocatalyst with the pollutants and further improve the catalytic efficiency.
[0017] (5) The prepared photocatalyst not only has a high initial catalytic activity, but also can maintain good catalytic performance after multiple uses, showing good recyclability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a graph showing the degradation efficiency of Rhodamine B / Acid Red 57 in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 2 are SEM and TEM images of the poly (N-vinyl caprolactam)@titanium dioxide hollow spheres of Example 1 of the present invention; Figure 3 The SEM image and EDX spectrum of the poly (N-vinyl caprolactam)@titanium dioxide crushed hollow spheres of Example 1 of the present invention are shown; Figure 4 This is an infrared curve diagram of the poly (N-vinyl caprolactam)@titanium dioxide hollow spheres of Example 1 of the present invention. DETAILED DESCRIPTION
[0019] The following embodiments of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are therefore only examples, and cannot be used to limit the protection scope of the present invention.
[0020] Example 1 (1) Using the classic Silica nanoparticles (SNPs) were prepared by 10.0 mL of deionized water was added to a beaker containing 58.5 mL of anhydrous ethanol, and the mixture was stirred at 25° C. for 5 min. Then, 3.125 mL of ammonia water was poured into the beaker and stirred thoroughly to obtain a mixed solution. 5.6 mL of tetraethyl silicate was added dropwise to the mixed solution, and the mixture was stirred and reacted at 25° C. for 1 h. After the reaction was completed, the crude product was centrifuged and washed three times with anhydrous ethanol and deionized water to obtain a white product. Finally, the white product was dried in a drying oven at 60° C. to obtain silica nanoparticles (SNPs). (2) Preparation of anatase titanium dioxide-coated silicon dioxide (SiO 2 @A-TiO 2 )Nanoparticles 0.8 g of silica nanoparticles were ultrasonically dispersed in 97.4 mL of anhydrous ethanol, 1.0 g of hexadecylamine and 1.79 mL of ammonia water were added to the suspension in sequence, and stirred at 25 ° C for 30 min, and then 2.2 mL of tetrabutyl titanate was added dropwise to the mixture, stirred at 25 ° C for 2 h, and aged at room temperature for 12 h; after the reaction, the crude product was centrifuged and washed three times with anhydrous ethanol and deionized water respectively to obtain a white product; the product was placed in a vacuum drying oven at 60 ° C to be fully dried to obtain amorphous titanium dioxide encapsulated silica (SiO 2 @Amorphous-TiO 2 ) nanoparticles; then, the amorphous titanium dioxide-coated silicon dioxide was placed in a muffle furnace and heated to 550°C at 5°C / min, reacted at this temperature for 6 hours, and naturally cooled to obtain anatase titanium dioxide-coated silicon dioxide (SiO 2 @A-TiO 2 ) nanoparticles; (3) Preparation of titanium dioxide hollow spheres Take 1.0g SiO 2 @A-TiO 2 The nanoparticles were ultrasonically dispersed into 60.0 mL of 1 mol / L sodium hydroxide solution and reacted at 60°C for 3 h. After the reaction, the crude product was centrifuged and washed three times with deionized water to obtain a white product. The product was placed in a constant temperature drying oven at 60°C and dried for 12 h to obtain titanium dioxide hollow spheres (TiO 2 -HSs); (4) Synthesis of ammonia functionalized titanium dioxide hollow spheres (TiO 2 -HSs-NH 2 ) 0.1 g of titanium dioxide hollow spheres (TiO 2 -HSs) and 3.0mL 3-aminopropyltriethoxysilane (APTES) were ultrasonically dispersed in a flask containing 50.0mL toluene, and refluxed at 70°C for 12h. After the reaction, the crude product was recovered by centrifugation and washed three times with anhydrous ethanol and deionized water respectively to obtain a white product; the product was placed in a vacuum drying oven at 25°C for 48h to obtain ammonia-functionalized titanium dioxide hollow spheres (TiO 2 -HSs-NH 2 ); (5) Synthesis of aldehyde-functionalized titanium dioxide hollow spheres (TiO 2 -HSs-CHO) 0.1 g TiO 2 -HSs-NH 2 Ultrasonic dispersion was carried out in a mixture of 6.0 mL of glutaraldehyde and deionized water (V:V = 1:2), and stirred at 25 °C for 4 h. After the reaction, the crude product was recovered by centrifugation and washed three times with anhydrous ethanol and deionized water to obtain a white product. The product was placed in a vacuum drying oven at 25 °C for 48 h to obtain aldehyde-functionalized titanium dioxide hollow spheres (TiO 2 -HSs-CHO); (6) Synthesis of poly (N-vinyl caprolactam)@titanium dioxide hollow sphere catalyst The hydrogen chloride gas prepared by the reaction of concentrated sulfuric acid and sodium chloride was passed into 50.0 mL of 1,4-dioxane. When the pH value of the system reached 5, 1.5 g of N-vinyl caprolactam (NVCL), 0.03 g of azobisisobutyronitrile (AIBN) and 0.02 g of mercaptoethylamine were added and ultrasonically dispersed uniformly. Under the same ultrasonic conditions, 0.3 g of aldehyde-functionalized titanium dioxide hollow spheres (TiO 2 -HSs-CHO), after ultrasonic treatment for a period of time, when the whole system is in a suspension state and there is no precipitation at the bottom, the air is evacuated and filled with nitrogen, stirred at 25°C for 12h, and then the temperature is raised to 68°C, and refluxed and stirred for 24h; after the reaction, the crude product is recovered by centrifugation and washed three times with anhydrous ethanol to obtain a white crude product; the crude product is ultrasonically dispersed in 20.0mL of an ammonia solution with a pH value of 7-8, and stirred at 25°C for 6h; after the reaction, the crude product is recovered by centrifugation and washed three times with deionized water to obtain a white product; the product is placed in a vacuum drying oven at 25°C and dried for 48h to obtain a poly (N-vinyl caprolactam@titanium dioxide hollow sphere catalyst) (PNVCL@TiO 2 -HSs).
[0021] Example 2 Carbon spheres with a diameter of 450 nm were used as templates instead of the silicon dioxide in Example 1. The preparation method was the same as that in Example 1 except that the template was removed by calcination at 550°C.
[0022] Comparative Example 1 TiO 2 -HSs-CHO preparation method is the same as step (1) to step (3) of Example 1; (4) 5.0 g of monomer N-vinyl caprolactam (NVCL) and 0.081 g of chain initiator azobisisobutyronitrile (AIBN) were added to a flask containing 50 mL of 1,4-dioxane in sequence. After ultrasonic dispersion, the mixture was evacuated and filled with nitrogen, and stirred at 25° C. for 30 min. Then, 10 mL of a 1,4-dioxane mixed solution containing 0.055 g of mercaptoethylamine was added to the flask. After evacuation and filling with nitrogen, the mixture was heated to 68° C. and refluxed for 24 h. After the reaction was completed, unreacted 1,4-dioxane was removed by rotary evaporation to obtain a white solid. The obtained solid was dissolved in dichloromethane, and then slowly added dropwise to diethyl ether for precipitation, filtered, and the above recrystallization process was repeated three times to obtain a crude product. The crude product was placed in a constant temperature vacuum oven at 25° C. and dried for 48 h to obtain a white solid PNVCL-NH 2 ; (5) At 25°C, 150.0 mg of PNVCL-NH 2 Ultrasonic dispersion was added to 20.0 mL of deionized water. 2 After complete dispersion, take 50.0 mg TiO 2 -HSs-CHO was ultrasonically dispersed into the above system. After a period of reaction, when the whole system was in a suspension state, the mixed solution was stirred for 4 hours. After the reaction was completed, the crude product was recovered by centrifugation and washed three times with deionized water to obtain a white product. The product was placed in a vacuum drying oven at 25°C and dried for 48 hours to obtain TiO 2 -HSs@PNVCL.
[0023] Comparative Example 2 Preparation of hollow titanium dioxide spheres (TiO 2 -HSs); its preparation method is the same as step (1) to step (3) of Example 1.
[0024] 1. Analysis of the photocatalytic performance of the thermosensitive polymer grafted on the inner wall of titanium dioxide hollow spheres The catalytic performance of the poly (N-vinyl caprolactam)@titanium dioxide hollow sphere catalyst of Example 1 was tested in a photoreactor. 0.25g poly(N-vinyl caprolactam)@titanium dioxide hollow sphere photocatalyst was ultrasonically dispersed into 100mL of 10mg / L rhodamine B or 100mL of 30mg / L acid red 57 solution. After the photocatalyst was completely dispersed, the mixed solution was exposed to a xenon light source for photocatalytic degradation. During the reaction, a certain amount of the suspension was drawn at fixed intervals, and after centrifugation, the absorbance of the supernatant sample was tested and the concentration of rhodamine B / acid red 57 and its degradation rate were calculated.
[0025] Grafting thermosensitive polymer (poly (N-vinyl caprolactam@titanium dioxide hollow sphere PNVCL@TiO 2 -HSs) to Rhodamine B degradation diagram ( Figure 1 ) can be seen from the figure that after 100 min of photocatalytic degradation, the titanium dioxide hollow spheres and the outer wall of the titanium dioxide hollow spheres grafted with the thermosensitive polymer (titanium dioxide hollow spheres@poly N-vinyl caprolactam TiO 2 -HSs@PNVCL) have photodegradation efficiencies of 77% and 88% respectively; while the degradation efficiency of the thermosensitive polymer grafted on the inner wall of the titanium dioxide hollow sphere (poly N-vinyl caprolactam @ titanium dioxide hollow sphere) reached 96%; after 100 minutes of photocatalytic reaction, the degradation rates of the three for acid red 57 were 50%, 67% and 78% respectively; therefore, compared with the first two, the thermosensitive polymer grafted on the inner wall of the titanium dioxide hollow sphere (poly N-vinyl caprolactam @ titanium dioxide hollow sphere) completed the same degradation effect in a shorter time, indicating that the composite material has better catalytic performance; the reasons for this result are: 1. Compared with the titanium dioxide hollow sphere, the grafting of the thermosensitive polymer on the inner wall of the titanium dioxide hollow sphere can expand the response ability of the composite material to visible light; 2. Compared with the material grafted on the outer wall, the composite material prepared by the present invention has a larger visible light response area and has good dispersibility in the aqueous phase when the water temperature changes.
[0026] 2. Material structure analysis of thermosensitive polymer grafted on the inner wall of titanium dioxide hollow sphere Grafting thermosensitive polymer (poly (N-vinyl caprolactam@titanium dioxide hollow sphere catalyst PNVCL@TiO 2 -HSs) Figure 2 ) can be seen that a layer of poly (N-vinyl caprolactam) grows on the inner surface of the titanium dioxide hollow sphere grafted with the thermosensitive polymer (poly (N-vinyl caprolactam @ titanium dioxide hollow sphere catalyst)).
[0027] During the ultrasonic treatment of the inner wall of titanium dioxide hollow sphere grafted with thermosensitive polymer (poly (N-vinyl caprolactam @ titanium dioxide hollow sphere catalyst), part of the sample will be destroyed. Figure 3 ) It can be seen that the outer wall contains three elements, Ti, O and C, and the inner wall contains five elements, Ti, O, C, N and S, which shows that the grafting only occurs on the inner wall of the hollow sphere.
[0028] UV-visible diffuse reflectance spectrum of thermosensitive polymer (poly (N-vinyl caprolactam @ titanium dioxide hollow sphere catalyst) grafted onto the inner wall of titanium dioxide hollow sphere ( Figure 4 ) can be seen that the titanium dioxide hollow spheres grafted with poly (N-vinyl caprolactam) have a stronger response to visible light, and therefore have a stronger visible light response ability than titanium dioxide hollow spheres under the same conditions, thereby producing more active species to degrade pollutants.
[0029] The above analysis shows that the thermosensitive polymer grafted onto the inner wall of titanium dioxide hollow spheres has high catalytic activity during photocatalytic degradation.
[0030] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a thermosensitive poly-N-vinyl caprolactam grafted titanium dioxide hollow sphere catalyst with high catalytic activity, characterized in that: Specific steps as follows: (1) Preparation of titanium dioxide-encapsulated silica nanoparticles or carbon spheres Ultrasonic dispersion of silica nanoparticles or carbon spheres in anhydrous ethanol, addition of hexadecylamine and ammonia, and dropwise addition of tetrabutyl titanate, wherein the mass volume ratio of the silica nanoparticles to the tetrabutyl titanate is 4:11 g / mL, to prepare anatase titanium dioxide-encapsulated silica nanoparticles or carbon spheres; (2) Preparation of titanium dioxide hollow spheres The anatase titanium dioxide-coated silicon dioxide nanoparticles are ultrasonically dispersed in a sodium hydroxide solution and reacted at 60° C. for 3 hours to obtain a crude product; the product is centrifuged, washed, and dried; or the anatase titanium dioxide-coated carbon spheres are calcined at 550° C. to obtain titanium dioxide hollow spheres; (3) Synthesis of ammonia functionalized titanium dioxide hollow spheres Ultrasonic dispersion of titanium dioxide hollow spheres and 3-aminopropyltriethoxysilane in toluene, wherein the mass volume ratio of the titanium dioxide hollow spheres to the 3-aminopropyltriethoxysilane is 0.1:3 g / mL, reflux reaction at 70° C. for 12 h to obtain a crude product, centrifugation, washing, and vacuum drying to obtain amino-functionalized titanium dioxide hollow spheres; (4) Synthesis of aldehyde-functionalized titanium dioxide hollow spheres Ultrasonic dispersion of ammonia-functionalized titanium dioxide hollow spheres into a glutaraldehyde aqueous solution, wherein the mass volume ratio of the ammonia-functionalized titanium dioxide hollow spheres to the glutaraldehyde aqueous solution is 0.1:6 g / mL, stirring and reacting at 25° C. for 4 h to obtain a crude product, which is centrifuged, washed, and vacuum-dried to obtain aldehyde-functionalized titanium dioxide hollow spheres; (5) Passing hydrogen chloride gas into 1,4-dioxane until the pH value is 5, adding N-vinylcaprolactam, azobisisobutyronitrile and mercaptoethylamine and ultrasonically dispersing them uniformly, then adding aldehyde functionalized titanium dioxide hollow spheres and continuing to ultrasonically disperse them uniformly, wherein the mass ratio of N-vinylcaprolactam, azobisisobutyronitrile, mercaptoethylamine and N-vinylcaprolactam@titanium dioxide hollow sphere composite material is 1.5:0.03:0.02:0.3, stirring for 12 hours at 25°C in a nitrogen environment, heating to 68°C and reflux stirring for 24 hours, centrifuging and washing to obtain a crude product; ultrasonically dispersing the crude product into an ammonia solution with a pH value of 7-8, stirring at 25°C for 6 hours, recovering by centrifugation, washing, and vacuum drying to obtain a poly N-vinylcaprolactam@titanium dioxide hollow sphere catalyst.
2. The method for preparing the temperature-sensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity according to claim 1, characterized in that: The mass volume ratio of the aldehyde functionalized titanium dioxide hollow spheres to 1,4-dioxane is 3:500 g / mL.
3. The method for preparing the temperature-sensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity according to claim 1, characterized in that: The silica nanoparticles are prepared using the classical Prepared by the method.
4. The method for preparing the temperature-sensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity according to claim 3, characterized in that: The preparation process of silica nanoparticles is as follows: deionized water is added to anhydrous ethanol, and after stirring evenly, ammonia water is poured into a beaker, and the volume ratio of anhydrous ethanol to ammonia water is 18.72:
1. After stirring evenly, tetraethyl silicate is added dropwise, and the volume ratio of tetraethyl silicate to ammonia water is 5.6:3.
125. The reaction is stirred at 25°C for 1 hour to obtain a crude product. After centrifugal separation and washing, it is dried in a drying oven at 60°C to obtain silica nanoparticles.
5. The method for preparing the temperature-sensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity according to claim 4, characterized in that: The volume ratio of the deionized water to anhydrous ethanol is 10:58.
5.
6. The method for preparing the temperature-sensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (2) is 1 mol / L.
7. The method for preparing hollow spheres of thermosensitive polymer poly N-vinyl caprolactam grafted titanium dioxide with high catalytic activity according to claim 6, characterized in that: The amount of the sodium hydroxide solution added is 60.0 mL of the sodium hydroxide solution per gram of anatase titanium dioxide-encapsulated silicon dioxide nanoparticles.
8. The method for preparing the temperature-sensitive poly (N-vinyl caprolactam) grafted titanium dioxide hollow sphere catalyst with high catalytic activity according to claim 1, characterized in that: The volume ratio of glutaraldehyde to deionized water in the glutaraldehyde aqueous solution is 1:2.